The functions of shared metacognitive regulation and their differential relation with collaborative learners' understanding of the learning content. (February 2022) - De Backer, Liesje; Van Keer, Hilde; Valcke, Martin
Abstract: By taking into account the functions of socially shared metacognitive regulation (SSMR) (i.e. the role that SSMR plays in the (dis)continuation of ongoing interaction), the present study sheds light on the differential effectiveness of SSMR. The study more particularly investigates how individual students' involvement in SSMR that confirms, changes, activates, or stops interaction, predicts their understanding of the learning content on the short and middle-long term, taking into account students' prior knowledge. Sixty university students were involved. Multilevel models were run to investigate the relation between individual students' engagement in the functions of SSMR and their conceptual understanding. Contributing to SSMR that changes and that activates collaborative learning appeared significantly positively related to students' immediate understanding of the learning content, whereas participating in SSMR that confirms or that stops ongoing interaction was not. Contributing to SSMR (regardless of its function) appeared not significant for predicting students' conceptual understanding on the middle-long term. Highlights: Shared metacognitive regulation promotes students' immediate understanding. The functions of shared metacognitive regulation determine its effectiveness. Shared regulation that changes or activates collaborative learning is important. The effectiveness of shared metacognitive regulation is not sustainable.